2015
DOI: 10.1002/btpr.2065
|View full text |Cite
|
Sign up to set email alerts
|

From osmotic second virial coefficient (B22) to phase behavior of a monoclonal antibody

Abstract: Antibodies are complex macromolecules and their phase behavior as well as interactions within different solvents and precipitants are still not understood. To shed some light into the processes on a molecular dimension, the occurring self-interactions between antibody molecules were analyzed by means of the osmotic second virial coefficient (B22 ). The determined B22 follows qualitatively the phenomenological Hofmeister series describing the aggregation probability of antibodies for the various solvent composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 69 publications
3
29
0
Order By: Relevance
“…In Figure , the crystallization slot according to George and Wilson defines the range of high crystallization probability. Comparing these conditions with the phase behavior of mAb04c, in Figure , the same picture arises like with salts . Most of these experiments show crystallization within this range, few do not separate and others are crystallizing below this range.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…In Figure , the crystallization slot according to George and Wilson defines the range of high crystallization probability. Comparing these conditions with the phase behavior of mAb04c, in Figure , the same picture arises like with salts . Most of these experiments show crystallization within this range, few do not separate and others are crystallizing below this range.…”
Section: Resultssupporting
confidence: 56%
“…The higher the net charge of the proteins the higher is the repulsion . This can be confirmed by the B 22 ‐results in pure buffer . From these B 22 ‐results, it can also be shown that the differences in B 22 ‐values for mAb04c in pure buffer from pH 7 to 9 are small, as additional attractive forces like hydrophobic interaction influence the proteins.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…The parameter characterizes solute‐solute and solute–solvent interactions (Rosenbaum and Zukoski, ). The B22 could be successfully correlated with crystallization slots as well as precipitation points (George and Wilson, ; Rakel et al, ; Ruppert et al, ; Wilson, ). Unfortunately, that could only be shown for ideal dilute solutions.…”
Section: Introductionmentioning
confidence: 99%